Why Should We Care about Care? : The Role of Childcare and Eldercare in Kosovo - Levin, Victoria; Munoz Boudet, Ana Maria; Rosen, Beth Zikronah; Aritomi, Tami; Flanagan, Julianna; Rodriguez-Chamussy, Lourdes (World Bank, Washington, DC, 2018)
This note examines the provision of childcare and eldercare in Kosovo with an emphasis on the availability, price, and quality of care, and suggests policy priorities that address the identified challenges. The analysis in this note is based on a study aimed at exploring childcare and eldercare in the Western Balkans region, drawing primarily from a new mixed-methods dataset, described in the following section, and building on relevant quantitative surveys and data sources specific to Western Balkans countries. The note is structured as follows: section two introduces the new, independent mixed methods data set that is the basis for the analysis and findings presented. Section three describes the use of formal care arrangements in Kosovo. Next, based on the analysis of perspectives both from families with care needs and from care providers and discussing the role of norms and perceptions of childcare and eldercare use, the following sections are dedicated to the description of supply and demand of childcare and eldercare, respectively. Sections four and five focuses on the supply and demand of childcare, and sections six and seven describe supply and demand of eldercare. Section eight concludes by examining what we know in terms of policies that can support families in informal care provision in a sustainable and incentive-compatible manner.